Manufactures Building steps and columns, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - Lee, James P. (James Patrick), 1894- (1909)
Caption on album: Views showing decorative details. Alaska-Yukon-Pacific-Exposition. PH Coll 760.4c To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number Scanned from a photographic print using a Microtek Scanmaker 9600XL at 100 dpi in JPEG format at compression rate 3 and resized to 768x600 ppi. 2008.